2021
DOI: 10.1101/2021.06.21.449206
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

L-form switching confers antibiotic, phage and stress tolerance in pathogenic Escherichia coli

Abstract: The bacterial L-form is induced by exposure to cell wall targeting antibiotics or innate immune effectors such as lysozyme and is likely to be important in many human infections. Here, we demonstrate that the osmotically fragile L-form is a distinct physiological state in Escherichia coli that is highly tolerant of oxidative stress and resistant to powerful antibiotics and common therapeutic bacteriophages. L-forms quickly revert (<20h) to their cell-walled state after antibiotic withdrawal, with apparently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…CWD variants of pathogenic E. coli strains similarly demonstrated upregulation of genes involved in oxidative stress responses and DNA repair/SOS response, and the CWD forms were shown to be resistant to oxidative stress [117]. RNA-seq analysis of Staphylococcus aureus CWD cells indicated genes involved in energy metabolism, stress responses, protein synthesis and virulence were upregulated [27].…”
Section: Requirements For Survival As a Cwd Variantmentioning
confidence: 99%
See 4 more Smart Citations
“…CWD variants of pathogenic E. coli strains similarly demonstrated upregulation of genes involved in oxidative stress responses and DNA repair/SOS response, and the CWD forms were shown to be resistant to oxidative stress [117]. RNA-seq analysis of Staphylococcus aureus CWD cells indicated genes involved in energy metabolism, stress responses, protein synthesis and virulence were upregulated [27].…”
Section: Requirements For Survival As a Cwd Variantmentioning
confidence: 99%
“…However, aerobic growth of CWD E. coli could be achieved in the presence of a ROS scavenger [116]. It has also been observed that E. coli isolates induced to a transient CWD state with meropenem varied, with three of four isolates tested having an upregulation of ElaB, an inner membrane protein regulated by RpoS and associated with protection against oxidative stress [117]. The isolate without elevated ElaB was still resistant to oxidative stress, suggesting an alternate pathway is used to protect against oxidative stress in this strain [117].…”
Section: Oxidative Stressmentioning
confidence: 99%
See 3 more Smart Citations